A Study of Social Stratification In France In 19th Century as Portrayed in `The Necklace ‘La Parure’` Short Story by Guy De Maupassant - Nurmalasari, Uning; Samanik, Samanik (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This study aims to reveal the social stratification in French in 19th century through the main character of The Necklace ?La Parure? short story by Guy de Maupassant. This research applies sociological approach by Karl Marx and Max Weber. Sociology is a science which attempts the interpretive understanding of social action in order thereby to arrive at a casual explanation of its course and effects. In accordance, the writer uses qualitative method to conduct the research aimed to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts people individually or in groups. Specifically, this study focuses to analyze social life of the main character in the short story by Guy de Maupassant consisting the act and desire in having a bourgeois life, and the social stratification which repress the main character at that time. Moreover, the research uses the library research to collect the data of social stratification.   A Study of Social Stratification In France In 19th Century as Portrayed in `The Necklace ?La Parure?` Short Story by Guy De Maupassant